METHODOLOGY OF TEACHING "WEB DESIGN (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
Teaching web design in academic lyceums requires a structured methodology that integrates theoretical concepts with practical skills to prepare students for the dynamic field of web development. This article presents a comprehensive methodology for teaching web design in academic lyceums, focusing on curriculum development, instructional strategies, assessment methods, and the integration of emerging technologies. By following this methodology, educators can effectively engage students, foster creativity, and equip them with the necessary skills to succeed in the rapidly evolving field of web design